Analisis Penyaluran Kredit, dan Kredit Macet terhadap Profitabilitas: Studi Keuangan Pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2023 - Maulani, Almah; Nor Norisanti; Asep M. Ramdan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analyze credit distribution and bad credit on profitability in the banking sector listed on the Indonesia Stock Exchange (BEI). The method used in this research is descriptive and associative research methods with a quantitative approach. The population in this research is banking sector companies listed on the Indonesia Stock Exchange (BEI) for the 2023 period, with the number of samples used in this research being 39 banking companies listed on the Indonesia Stock Exchange for the 2023 period. The data collection technique used is by using data secondary obtained from documentation and literature study. By using the perposive sampling method. Using IBM SPSS Version 25 software, as a data analysis technique tool. The results of this research show that the credit distribution variable (X1) has a positive and significant effect on profitability, and the bad credit variable (X2) has a negative and significant effect on profitability. So all hypotheses are accepted